Relationship between aconitase gene expression and sporulation in Bacillus subtilis. - Dingman, D W (1987)
The citB of Bacillus subtilis codes for aconitase (D. W. Dingman and A. L. Sonenshein, J. Bacteriol. 169:3060-3065). By direct measurements of citB mRNA levels and by measurements of beta-galactosidase activity in a strain carrying a citB-lacZ fusion, we have examined the expression of citB during growth and sporulation. When cells were grown in nutrient broth sporulation medium, citB mRNA appeared in mid- to late-exponential phase and disappeared by the second hour of sporulation. This timing corresponded closely to the kinetics of appearance of aconitase enzyme activity. Decoyinine, a compound that induces sporulation in a defined medium, caused a rapid simultaneous increase in aconitase activity and citB transcription. After decoyinine addition, the rate of increase in aconitase activity in a 2-ketoglutarate dehydrogenase (citK) mutant and in a citrate synthase (citA) mutant was significantly less than in an isogenic wild-type strain. This is apparently due to a failure to deplete 2-ketoglutarate and accumulate citrate. These metabolites might act as negative and positive effectors of citB expression, respectively. Mutations known to block sporulation at an early stage (spo0H and spo0B) had no appreciable effect on citB expression or aconitase activity. These results suggest that appearance of aconitase is stimulated by conditions that induce sporulation but is independent of certain gene products thought to act at an early stage of sporulation.